2016
DOI: 10.1007/s00204-016-1880-y
|View full text |Cite|
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor signaling modifies Toll-like receptor-regulated responses in human dendritic cells

Abstract: Currently, it is not well understood how ligands of the Aryl hydrocarbon Receptor (AhR) modify inflammatory responses triggered by Toll like receptor (TLR) agonists in human dendritic cells (DCs). Here, we show that AhR ligands 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), the tryptophan derivatives 6-formylindolo[3,2-b]carbazole (FICZ), Kynurenine (kyn), and the natural dietary compound Indole-3-carbinole (I3C) differentially modify cytokine expression in human monocyte-derived DCs (MoDCs). The results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 54 publications
(82 reference statements)
6
43
0
1
Order By: Relevance
“…Although we observed that AhR activation in keratinocytes by S. epidermidis did not directly influence NF-κB activation, we found that activation of both transcription factors, NF-κB and AhR, were crucial for the S. epidermidis-mediated induction of IL-1β in keratinocytes. This is in concordance with the necessity of NF-κB and AhR for IL-1β expression in TLR-and M. tuberculosis-activated dendritic cells and macrophages [40,41].…”
Section: Discussionsupporting
confidence: 87%
“…Although we observed that AhR activation in keratinocytes by S. epidermidis did not directly influence NF-κB activation, we found that activation of both transcription factors, NF-κB and AhR, were crucial for the S. epidermidis-mediated induction of IL-1β in keratinocytes. This is in concordance with the necessity of NF-κB and AhR for IL-1β expression in TLR-and M. tuberculosis-activated dendritic cells and macrophages [40,41].…”
Section: Discussionsupporting
confidence: 87%
“…To the contrary, our data showed that LPS could not induce Ahr expression (data not shown) and that AHR-dependent Cyp1a1 induction was inhibited in these cells. However, similar to what has been reported in moDCs [45], we also observed that AHR antagonized some proinflammatory cytokines (e.g., IL-6, CCL3) but enhanced the production of others (e.g., IL-8). Likewise, AHR activation increased the expression of IL-23 in M-CSFderived macrophages [55].…”
Section: Discussionsupporting
confidence: 91%
“…6C). In human moDCs, AHR has been reported to enhance the production of IL-1b and IL-8 [45], contrary to its inhibitory effect on other proinflammatory cytokines [34]. Although we were unable to detect significant production of IL-1b in GM-MDMs (data not shown), we too found that AHR activation by FICZ significantly enhanced the production of IL-8 in GM-MDMs stimulated with LPS ( Fig.…”
Section: Ahr Activation Regulates the Proinflammatory Cytokine Responmentioning
confidence: 54%
“…Indeed, AhR plays an important role in the human immune system [9] and its interaction with the TLR/NF-κB signaling pathway has recently been elucidated [11-13]. The presence of bacterial originating TLR2 ligands seems to be crucial for detoxification of luminal carcinogens by CYP1A1 in the intestine and indicates a complex interplay between the immune system of the host and intestinal bacteria with detoxification mechanisms [23].…”
Section: Discussionmentioning
confidence: 99%
“…2,3,7,8-Tetrachlorodibenzo- p -dioxin (TCDD) is a high-affinity AhR ligand that is frequently used to investigate biological processes impacted by AhR activation [10]. In addition, close interactions between TLRs, NF-κB, and the AhR signaling pathway have been studied in human dendritic cells [11] and macrophages [12, 13], which contribute to immune dysfunction, metabolism of xenobiotics, and carcinogenesis [14]. …”
Section: Introductionmentioning
confidence: 99%